Analysis of Various Options for Balancing Power Systems’ Peak Load - Henryk Majchrzak; Michał Kozioł (Energies, 2021)
The balancing of the power of the Polish Power System (KSE) is a key element in ensuring the safety of electric energy supplies to end users. This article presents an analysis of the power demand in power systems (PS), with emphasis on the typical power variability both in subsequent hours of the day and on particular days and in particular months each year. The methodology for calculating the costs of electric energy undelivered to the end users and the amount of these costs for KSE is presented. Different possibilities have been analyzed for balancing power systems’ peak load and assumptions have been formulated for calculating the amount of the related costs. On this basis, a comparative analysis has been made of the possibility to balance peak load using operators’ system services, trans-border connections, and various energy storage solutions. On the basis of the obtained results, optimal tools have been proposed for market-based influence from transmission and distribution system operators on energy market participants’ behaviors in order to ensure the power systems’ operating safety and continuous energy deliveries to end users.